Workload-Based Medical Specialist Planning in Public Hospitals: The Case of Kocaeli - (:unkn) unknown (TURKIYE ORTA DOGU AMME IDARESI ENSTITUSU, 2016)
The human factor, which is the primary input for the provision of high quality health service, should be planned effectively. The first and most important stage of human resource planning is to identify, the number of work force required. In this study, Workload Indicators of Staffing Need (WISN) developed by the World Health Organization (WHO) has been used. The aim of the study is to determine the number of medical specialists needed in public hospitals in Kocaeli. based on workload To this end, it has been attempted to build a model in order to determine the actual number of medical specialists required, to provide balanced distribution on internal, local and provincial level in public hospitals, and to provide support health managers and planners with tools for effective human resources planning in public health sector.
Keywords: Medical specialists' workload; medical specialist planning; health labour force; WORKFORCE; HEALTH